Evaluation of the Value of Fine Needle Aspiration Cytology and Cell Morphology in Determining the Histogenesis of Pancreatic Lesions With Review of Literature, Overview and Cytological Experience of 25 Years: Original Research - Soudah Bisharah; Abbas Mahmoud (Health Science Reports)
ABSTRACT Background and Aims Benign lesions, inflammation, cysts and pseudocysts, as well as neoplasms of the exocrine and endocrine parts of the pancreas can be easily identified using cytological methods. The sensitivity and specificity can be increased with the help of additional examination methods. The sensitivity of intraoperative rapid cytology reaches about 99%. In the literature, the sensitivity reaches an average of about 85% for biopsies. The method is easy to use, has very low complication rates (1%–2%) and is safe for the patient. Methods 1290 cytological samples from pancreatic lesions were processed in the institute of pathology at Hannover Medical School (MHH), as cytological smears and stained with Giemsa and PAS stains as conventional methods. They were compared with the histological specimens that were processed at the same institute. Immunocytochemistry and molecularpathology have been processed only in selected cases. In general, it is routine in the university that the patients give their written consent to participate in clinical studies. The local ethics committee has stated that there is no need for approval due to the retrospective nature of the study. Results In this work, we detected 20.077% malignant lesions, 63.333% benign findings and inflammation, 7.441% pseudocysts and cysts. About 9.147% samples were unrepresentative due to insufficient number of cells. Conclusion This work will highlight the importance of fine aspiration cytology (FNAC) of suspicious pancreatic lesions, its possibilities and limitations in routine diagnostics with discussing the differential diagnoses, pointing to its great value and safety for patients. FNAC is the gold standard, its power is strongly associated with high specificity and sensitivity in the diagnosis of pancreatic lesions, and is very useful in the differential diagnosis between malignant and inflammatory lesions in pancreas.